Chronic Monosodium Methylarsonate (MSMA) exposure induces oxidation of Low Density Lipoprotein (LDL) and early atherosclerosis development - Adekunle, Ishola Afeez; Abdullah, Nor Zamzila; A.Talib, Norlelawati; Muhammad, Siti Aeshah @ Naznin; Buyong, Zunariah; Myint, Yi Yi; Mohamed, Abdul Hadi; Samsuddin, Niza; Abdul Ghani, Radiah (2015)
Monosodium methylarsonate (MSMA) is a potent organoarsenical used as herbicides in many countries. Human are particularly exposed by drinking of contaminated water. Epidemiological studies have linked high chronic arsenic exposure with cardiovascular diseases but the mechanism is not clear. Studies investigating the effects of MSMA are scarce as previous studies are focusing more on the effects of inorganic arsenic. Hence, this study aimed to investigate the effects of oral MSMA on atherosclerosis development in rats through its effects of PON1 enzyme and oxidized-LDL (Ox-LDL). Materials & Methods: Twenty-four male Sprague-Dawley rats were divided into three groups (n=8) including a control group. Treatment groups 1 and 2 were given oral MSMA of 42.13 and 63.30 mg/kg body weight respectively every day for 120 days. Serum PON1 activities and Ox-LDL level were measured. Aorta were microscopically evaluated after staining with Haematoxylin and Eosin (H&E), Verhoef Van Gieson (VVG) as well as with immunohistochemistry VCAM-1 and ICAM-1. Results: Our results revealed a significantly (p<0.05) higher Ox-LDL level and lower PON1: Ox-LDL ratio among the MSMA treated groups as compared to that of control group. Both MSMA treated groups also showed positive early atherosclerosis changes microscopically with positive VCAM-1 and ICAM-1 expression. Conclusions: The study highlighted that Chronic MSMA exposure affects the PON-1 activities and promotes LDL oxidation. The development of early atherosclerosis seen in chronic MSMA exposure may be explained by inability of PON1 to hydrolyze Ox-LDL.